Early Nutrition and Cognition in Peru - Ingo Outes-Leon; Catherine Porter; Alan Sanchez (Inter-American Development Bank (IDB), 2011)
This paper examines the causal link between early childhood nutrition and cognition, applying instrumental variables to sibling-differences for a sample of pre-school aged Peruvian children. Child-specific shocks in the form of food price changes and household shocks during the critical developmental period of a child are used as instruments. The analysis shows significant and positive returns to early childhood nutritional investments. An increase in the Height-for-Age z-score of one standard deviationkeeping other factors constanttranslates into increases in the Peabody Picture Vocabulary Test (PPVT) score of 17-21 percent of a standard deviation. The period of analysis includes the recent global food price crisis that also affected Peru between 2006 and 2008. This therefore is also a quantification of the nutritional and subsequent cognitive costs of food prices on the sample, which could be magnified in later years.
Keywords: I12; I20; J13; 330